Platelet-rich Plasma or Autologous Blood Do Not Reduce Pain or Improve Function in Patients with Lateral Epicondylitis: A Randomized Controlled Trial. Issue 8 (August 2020) - Linnanmäki, Lasse; Kanto, Kari; Karjalainen, Teemu; Leppänen, Olli V.; Lehtinen, Janne
Abstract: Background: Platelet-rich plasma (PRP) and autologous blood are commonly used therapies for lateral epicondylitis, but the evidence from randomized, placebo-controlled trials is conflicting. Thus, it is still unclear if patients benefit from these treatments. Questions/purposes: In the setting of a randomized, placebo-controlled trial, we compared PRP, autologous blood, and saline injections in the treatment of lateral epicondylitis with respect to: (1) VAS pain scores, and (2) functional outcomes (DASH score and grip strength) 1 year after treatment. Methods: We performed a parallel-group, randomized, controlled participant- and assessor-blinded study including adults with clinically diagnosed lateral epicondylitis. We defined lateral epicondylitis as pain in the lateral humeral epicondyle area exacerbated during resisted wrist extension and epicondyle compression. The participants were recruited from a secondary referral center, after not responding to initial nonoperative treatment. Patients with other concomitant upper-limb symptoms and surgical treatment of the elbow were excluded. Randomization sequence was generated with computer software and concealed from the investigators. We randomized 119 participants to receive an injection of PRP, autologous blood, or saline (1:1:1) in the proximal insertion of the extensor carpi radialis brevis muscle; 40 participants received PRP, 40 received autologous blood, and 39 received a saline injection. To prepare the PRP, we collected venous blood with a syringe kit followed by centrifugation, whereas autologous blood group received unprepared blood injection. Two unblinded investigators gave injections while the participant was unable to see the injection. There was no formal postinjection rehabilitation protocol and the use of NSAIDs was similar between different treatment arms. Follow-up visits were at 4, 8, 12, 26, and 52 weeks after the injection. The primary outcome measure was improvement in pain, measured with VAS scale (without specification as to whether the pain was activity related or at rest; range 0-10; a higher score indicates worse pain; the minimum clinically important difference [MCID] on the 10-cm scale was 1.5 cm), from baseline to 52 weeks. The secondary outcomes were the DASH score (range 0-100; a higher indicates a poorer outcome, and the MCID was 10.2 points) and grip strength. All patients were included in the analyses, and analyses were performed using the intention-to-treat principle. There was no crossover between treatment groups. At 52 weeks, nearly all (95% [38 of 40]) participants in autologous blood group were available for analysis whereas 78% (31 of 40) and 82% (32 of 39) were available in PRP and saline groups. This study was registered at ClinicalTrials.gov and funded by the local hospital district. With 40 patients in each group, we had 80% power to detect a clinically important improvement in pain (1.5 cm on the 10-cm VAS pain scale). Results: There were no clinically important differences in the mean VAS pain or DASH scores among the groups at any timepoint. At 52 weeks, the mean difference in the VAS score for pain was -0.2 (95% CI -1.5 to 1.1; p = 0.75) for PRP versus saline and 0.5 (95% CI -0.7 to 1.7; p = 0.40) for autologous blood versus saline. The corresponding mean differences in the DASH score were 0.0 (95% CI -9.2 to 9.2; p > 0.99) and 7.7 (95% CI -1.3 to 16.7; p = 0.09) and those for grip strength were 1.4 kg (95% CI -3.3 to 6.1; p = 0.56) and -0.2 kg (95% CI -5.0 to 4.5; p = 0.92). No complications occurred because of the injections. Conclusions: PRP or autologous blood injections did not improve pain or function at 1 year of follow-up in people with lateral epicondylitis compared with those who were given a saline injection. However, because the 95% CIs did not exclude the MCID in VAS scores for autologous blood versus saline at 52 weeks, it is possible that a larger study could identify a between-group difference that we missed, but the effect size of that difference (based on our findings), even if present, is likely still to be small. Until or unless future randomized trials convincingly show a benefit either to PRP or autologous blood injections, we recommend against their use in patients with lateral epicondylitis. Level of Evidence: Level II, therapeutic study.